Assessment of predation by the West Coast rock lobster (Jasus lalandii) : relationships among growth rate, diet and benthic community composition, with implications for the survival of juvenile abalone (Haliotis midae) - Mayfield, Stephen (Department of Biological Sciences, 2014)
Bibliography: leaves 195-213.